2020
DOI: 10.3389/fcimb.2020.00004
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Causative Human Papillomavirus Type in Tissue Specimens of Common Warts Based on Estimated Viral Loads

Abstract: Background: Assessment of human papillomavirus (HPV) type-specific viral load (VL) is a valid tool for determining the etiology of HPV-related skin tumors, especially when more than one HPV type is detected within one lesion.Methods: The causative HPV type was determined in 185 fresh-frozen tissue specimens of histologically confirmed common warts (CWs) collected from 121 immunocompetent patients. All tissues were tested using the type-specific quantitative real-time polymerase chain reactions (PCR) for the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(44 citation statements)
references
References 39 publications
4
39
0
Order By: Relevance
“…HPV135 infection has been demonstrated in four cases of common warts, at concentrations of five to 539 viral copies/10 4 cells that are much lower than previously suggested for viruses that are etiologically associated with the development of such lesions [ 35 , 38 ]. Interestingly, HPV135 has been detected in both skin warts undoubtedly caused by HPV179 and 184, respectively [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPV135 infection has been demonstrated in four cases of common warts, at concentrations of five to 539 viral copies/10 4 cells that are much lower than previously suggested for viruses that are etiologically associated with the development of such lesions [ 35 , 38 ]. Interestingly, HPV135 has been detected in both skin warts undoubtedly caused by HPV179 and 184, respectively [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…HPV179 was originally identified in a common wart of an immunocompromised patient and, based on the high viral load and absence of the most common etiological factors of common warts (HPV2, 27, 57) [ 35 ], it was characterized as its most probable causative agent [ 8 ]. Subsequently, seven additional HPV179-isolates, four from common warts (4/94; 4.2%) and single isolates from eyebrow hair follicles (1/100; 1.0%), cutaneous SCC (1/50; 2.0%), and BCC (1/51; 1.96%), were detected in our previous study [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the MfuPV2 viral load in tissue sample of the benign penile lesion of a Japanese macaque was estimated at 10.37 viral DNA copies per single host cell, which is similar to the low-risk HPV6 viral load in samples of genital warts, with values ranging from 2 to 870 viral DNA copies per single human cell [56]. In addition, based on the estimates of viral load of cutaneous HPV types measured in common skin warts containing a single HPV type and a clear bimodal distribution of the viral loads, the cutoff value for the determination of the causative HPV type was previously set at one HPV DNA copy per single human cell [57]. The comparison of MfuPV1 and MfuPV2 viral loads to viral load data described previously for other Alpha-PV types in similar neoplastic lesions, and the detection of only MfuPV1 and MfuPV2 in the original neoplasms using PCR in a combination with broad-spectrum CODEHOP primers strongly suggest a mucosal tissue tropism of both novel PV types and their causative role in the development of these particular neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…HPV1, HPV41) HPV types. 13,14 Studies in adults have shown that certain HPV types appear to be largely sitespecific for warts at mucosal or cutaneous sites. 15 In children, horizontal transmission allows that cutaneous HPV types, which typically cause extra-genital common warts, are transferred to the genital area, where they can cause AGW.…”
Section: Introductionmentioning
confidence: 99%
“…HPV4) or mu/nu (e.g. HPV1, HPV41) HPV types 13,14 . Studies in adults have shown that certain HPV types appear to be largely site‐specific for warts at mucosal or cutaneous sites 15 .…”
Section: Introductionmentioning
confidence: 99%